Identification of fungal phyto-pathogens by Fourier-transform infrared (FTIR) microscopy - Erukhimovitch, V.; Tsror, L.; Hazanovsky, M.; Talyshinsky, M.; Mukmanov, I.; Souprun, Y.; Huleihel, M. (International Journal of Agricultural Technology, 2005)
Fungi are considered as serious pathogens to many plants and can cause a severe economic damage. Early detection and identification of these pathogens is very important and might be critical for their control. The available methods for identification of fungi are time consuming and not always very specific. Fourier-transform infrared (FTIR) microscopy is proved to be a reliable and sensitive method for detection of molecular changes in cells. In the present study we used FTIR microscopy as a sensitive and effective assay for the detection and discrimination between different genera of fungi. Our results showed significant spectral differences between the various examined fungal genera.